New Perspective of Kottamchukkadi Taila: A Critical Review - Sharma, Sonam; Thorwat, V K (International Research Journal of Ayurveda & Yoga, 2022)
Kottamchukkadi taila is an important Snehan Kalpana (oil formation) mentioned in ayurveda text prepared from Chincharas (tamarind juice) and dadhi (curd). It contains more than 9 herbs. It is ayurvedic oil used in the treatment of Vata disorder causing neuro muscular pain, sciatica, spondylosis etc. This oil formulation based on Kerala ayurveda practice. It helps to relieve pain and inflammation. It is used in arthritis, sciatica, ankle sprain, blunt injury of knee, tennis elbow etc. It is also useful in intercostals neuropathy, numbness, pain, stiffness, muscle and joint pain. It acts like Lekhana, Srotoavorodhagna Shothahar etc. Present study aimed to compile all the available literature regarding its use method of preparation.